Exploring the Relationship Between Child Maltreatment, Intimate Partner Violence Victimization, and Self-Injurious Thoughts and Behaviors. Issue 7 (9th August 2018) - Caron, Angela; Lafontaine, Marie-France; Bureau, Jean-François
ABSTRACT: Child maltreatment is considered a significant risk factor for young adult self-injury; however, the mechanisms that underlie this relationship are not yet understood. To elucidate this association, the mediating role of intimate partner violence victimization in the relationship between child maltreatment and self-injurious thoughts and behaviors was investigated. The sample consisted of 406 young adults (346 females; M age = 19.87 years; SD = 1.72) involved in a couple relationship. Results of bootstrapping procedures demonstrated that intimate partner violence victimization mediated the relationship between child maltreatment and self-injurious behaviors but did not mediate the association between child maltreatment and self-injurious thoughts. Results suggest that young adults with a history of child maltreatment may be more likely to be exposed to IPV victimization, which, in turn, is associated with the use of self-injurious behaviors, but not the use of self-injurious thoughts. Findings highlight the utility of examining models that incorporate distal and proximal factors contributing to self-injury, and provide direction toward better understanding the relationship experiences of self-injuring young adults.